Implementasi Sistem Penentuan Kesegaran Daging Sapi Lokal Berdasarkan Warna dan Kadar Amonia Dengan Metode Jaringan Saraf Tiruan Berbasis Embedded System - Hamdan Bagus Firmansyah; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Beef is the most meat that consumed by humans. High consumption of beef along with the high price of beef has caused many butcher mix fresh beef with rotten beef. The impact of consuming rotten meat can be diarrhea and poisoning. From these problems we need related research to make meat freshness detection systems to reduce disadvantages in the society. In this study the parameters used were color and ammonia levels. This study aims to design a system for determining local beef freshness based on color and ammonia levels. The process of determining the freshness of the meat is obtained from the reading results of the TCS3200 color sensor and the MQ135 gas sensor by the Arduino Uno microcontroller using the Artificial Neural Network method. Accuracy results from the tests carried out obtained a system for determining the freshness of beef based on color and ammonia levels in local beef with artificial neural network methods tested with the number of training data as much as 81 data and test data as many as 27 data worth 92.5%.